HUBUNGAN AGAMA DAN NEGARA: Konteks Ke-Indonesiaan - Abdullah, Abdullah (JPP (Jurnal Politik Profetik), 2014)
Establishing a country according to Islamic perspective is a must. But the extent to which an Islamic country should be formed, is not considered significant as long as Islamic values are applied. This is to avoid contradiction between the essence of Islamic teachings and the immoral attitude of some Muslims. The differences between the true essence of Islamic teachings and the attitude of Muslims in their daily life would create discrepancy. The concept of democracy is in line with Islam, since Islam is a religion which supports truth, justice, law enforcement, freedom in all aspects of life including religion, speech, human rights and many others. Human rights are fundamental aspect to support since it is obtained from the early life of human beings as a divine gift. In this case, Islam as a divine religion considers human rights as essential needs of human beings. Islam treats all human beings as equal before the law, justice and freedom.